Impact of Environment, Social, and Governance Pillars on Firm Value in Oil and Gas Sector - Adiwardhana, Gusman; Rahmawati, Rahmawati; Sangka, Khresna Bayu; Prasetyani, Dwi; Kurniawati, Estetika Mutiaranisa; Jayanti, Risca Dwi (International Journal of Energy Economics and Policy, 2025)
This research was carried out to investigate environment, social, and governance (ESG) impact on firm value in oil and gas sector using good management theory. The research uses 105 unbalanced panel data obtained from oil and gas sector between 2018 and 2022. Bloomberg ESG disclosure scores and audited annual reports are obtained and analyzed applying the pooled ordinary least square (OLS) framework, with heteroscedasticity strong standard errors. Country and year-fixed effects are considered to mitigate systematic variances in firm value across each pillar of ESG. A positive relation exists on aggregate ESG and firm value. The results show that higher quality of ESG reporting increases firm value in oil and gas sector. A robustness test is also performed to analyze each pillar in ESG score. There is a positive correlation between social and governance pillars as well as firm value. In contrast, environment pillar is not individually related to firm value. According to good management theory, increased investment in firm social responsibility signifies a superior standard of management and improved financial performance. Differences in ESG practices across countries present an interesting opportunity to obtain the ESG correlation by Bloomberg Score and firm value.